2009
DOI: 10.1007/s00360-009-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic depression during aestivation does not involve remodelling of membrane fatty acids in two Australian frogs

Abstract: Changes in membrane lipid composition (membrane remodelling) have been associated with metabolic depression in some aestivating snails but has not been studied in aestivating frogs. This study examined the membrane phospholipid composition of two Australian aestivating frog species Cyclorana alboguttata and Cyclorana australis. The results showed no major membrane remodelling of tissue in either frog species, or in mitochondria of C. alboguttata due to aestivation. Mitochondrial membrane remodelling was not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…For example, this has been suggested for the content of adenine nucleotide translocase (Talbot et al, 2004;Brand et al, 2005;Shabalina et al, 2006). In amphibians, some studies have shown that the mitochondrial inner membrane surface area might be greater in the mitochondria of liver and muscle from smaller species (Brookes et al, 1998;Hulbert et al, 2006;Berner et al, 2009). Therefore, the relationship between M b and proton conductance in frogs might be due to variation in the mitochondrial inner membrane.…”
Section: Discussionmentioning
confidence: 96%
“…For example, this has been suggested for the content of adenine nucleotide translocase (Talbot et al, 2004;Brand et al, 2005;Shabalina et al, 2006). In amphibians, some studies have shown that the mitochondrial inner membrane surface area might be greater in the mitochondria of liver and muscle from smaller species (Brookes et al, 1998;Hulbert et al, 2006;Berner et al, 2009). Therefore, the relationship between M b and proton conductance in frogs might be due to variation in the mitochondrial inner membrane.…”
Section: Discussionmentioning
confidence: 96%
“…Frogs were fed ad libitum with vitamin-fortified crickets, although most refused food during the first week in September and so feeding was thereafter suspended. The crickets were the same as those used to feed the Ohioan frogs in an effort to eliminate potential effects of diet on membrane lipid composition (Berner et al 2009;Stanley-Samuelson et al 1985). Following acclimatization, several frogs were sampled immediately ("fall"; n = 7), whereas most were kept at 4 °C, in darkness, for 9 weeks in simulated hibernation until sampled in mid November ("winter"; n = 7).…”
Section: Methodsmentioning
confidence: 99%
“…We extracted lipids from the isolated membranes following the procedure of Berner et al (2009), which is a variant of the Folch method that uses a solvent system of chloroform-methanol 2:1 (v/v) with 0.01 % (w/v) butylated hydroxytoluene (BHT) as an antioxidant. The phases were separated with 1 M H 2 SO 4 .…”
Section: Lipid Extraction and Thin Layer Chromatographymentioning
confidence: 99%
“…Em esquilos, dietas com alto teor de PUFA causam aumento do número de animais que entram em torpor, redução da faixa de regulação da temperatura corpórea e da taxa metabólica durante a depressão metabólica e um aumento da duração das fases de torpor e da taxa de sobrevivência durante a hibernação (DARK, 2005;FRANK, 1992 EBERSPACHER et al, 2005). Assim como nos teiús, a estivação em dois sapos do gênero Cyclorana e no caracol Helix aspersa não envolve alterações da composição de ácidos graxos dos fosfolipídios dos tecidos ou da membrana mitocondrial (BERNER et al, 2009;BISHOP et al, 2002). Em animais ectotérmicos, capazes de ingressar em um estado de dormência em temperaturas ambientais amenas, como os teiús e exemplos acima, variações intraespecíficas da taxa metabólica talvez estejam relacionadas a mudanças mais sutis em ácidos graxos e fosfolipídios que têm o potencial de modular a atividade de proteínas específicas como no caso da interação entre a CCO e a cardiolipina, e não a mudanças de composição abrangentes, que resultam em alteração das propriedades físicas das membranas.…”
Section: Composição Dos Lipídios Neutros E Polaresunclassified
“…No entanto, outras evidências de um papel dos ajustes da composição de ácidos graxos na regulação metabólica durante a dormência sazonal não são conhecidas. A dormência em dois sapos do gênero Cyclorana e no caracol Helix aspersa não envolve alterações da composição de ácidos graxos dos fosfolipídios dos tecidos ou da membrana mitocondrial (BERNER et al, 2009;BISHOP et al, 2002). Do mesmo modo, em um recente estudo Haddad (2007) mostrou que a dormência sazonal nos teiús aparentemente não envolve amplas alterações dos ácidos graxos polares do fígado e músculo esquelético, como proposto por Hulbert & Else (2000).…”
Section: Introductionunclassified